(untitled) (Revista Sistemas de Producción Agroecológicos, 2012)
In order to further our understanding of phytopharmacology Colombia, particularly those present in the eastern plains region, the species was chosen for further Momordica charantia in chemical composition and thus establish a potential medical utility. This analysis was performed preliminary phytochemical, which evaluated the presence of the main groups of secondary metabolites associated with biological activity, namely: alkaloids, flavonoids, triterpenoids, anthracene glycosides, cardiogenic glycosides and saponins. Was detected the presence of alkaloids in Momordica collected at the University of the Llanos, these compounds are widely known for their antidiabetic properties. It is also remarkable the presence of triterpenes, which are attributed antiparasitic properties, anticancer, anti-HIV, antidiabetic and antifeedant. It also showed the presence of cardiogenic glycosides that may have antiviral activities. The results of this work are really useful as a first approximation to the extension of chemical knowledge and the potential use fullness of the species in this area of Colombia, with medicinal properties to human health and animal-that allow the efficient use of resources country’s natural as a source of regional and national development.